2017
DOI: 10.18332/tpc/70088
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Mobile Apps for Smoking Cessation: Α Review

Abstract: INTRODUCTION Smartphone-based smoking cessation interventions are increasingly used around the world. However, the effects of smartphone applications on applicability and efficacy on cessation rate and prevention of relapses are not often evaluated. Therefore, this review aims to assess the evidence on effectiveness of smartphone applications as an intervention tool for smoking cessation support. METHODS We conducted the search using Ovid Medline/PubMed, CENTRAL and Scopus databases dated (January 2007-June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 52 publications
2
48
1
2
Order By: Relevance
“…Less research has been performed around the use of smoking cessation apps on smartphones. Nevertheless, a review of eight studies of such apps indicated favourable quit rates for app users in the range of 13 to 24% [4]. Others subsequent studies have also reported favourable results [5,6], but the first full randomised controlled trials (RCT) were not published until 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Less research has been performed around the use of smoking cessation apps on smartphones. Nevertheless, a review of eight studies of such apps indicated favourable quit rates for app users in the range of 13 to 24% [4]. Others subsequent studies have also reported favourable results [5,6], but the first full randomised controlled trials (RCT) were not published until 2018.…”
Section: Introductionmentioning
confidence: 99%
“…This study focuses on a qualitative exploration of the experiences of trial participants who interacted with the CTC. Trials evaluating smoking cessation apps are emerging, with recent systematic reviews summarizing preliminary evidence that smoking cessation apps are effective [ 12 , 13 ]. Although this quantitative evidence is important, qualitative data that capture end-users’ perspectives are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…[23] Two of the apps examined were supported by small randomized controlled trials [14,24] and one was an observational study [25].…”
Section: Introductionmentioning
confidence: 99%